Cholera outbreaks in sub-Saharan Africa during 2010-2019: a descriptive analysis. (September 2022) - Zheng, Qulu; Luquero, Francisco J; Ciglenecki, Iza; Wamala, Joseph F; Abubakar, Abdinasir; Welo, Placide; Hussen, Mukemil; Wossen, Mesfin; Yennan, Sebastian; Keita, Alama; Lessler, Justin; Azman, Andrew S; et al.
Highlights: Cholera outbreaks affected 2% of the sub-Saharan Africa populations in the 2010 decade. 692 outbreaks were identified in 492 districts with a systematic definition. Larger outbreaks were associated with longer durations and lower reported mortality. Population density was not always associated with severe cholera outbreak outcomes. Surveillance needs to be enhanced to improve cholera outbreak monitoring. Abstract: Background: Cholera remains a public health threat but is inequitably distributed across sub-Saharan Africa. Lack of standardized reporting and inconsistent outbreak definitions limit our understanding of cholera outbreak epidemiology. Methods: From a database of cholera incidence and mortality, we extracted data from sub-Saharan Africa and reconstructed outbreaks of suspected cholera starting in January 2010 to December 2019 based on location-specific average weekly incidence rate thresholds. We then described the distribution of key outbreak metrics. Results: We identified 999 suspected cholera outbreaks in 744 regions across 25 sub-Saharan African countries. The outbreak periods accounted for 1.8 billion person-months (2% of the total during this period) from January 2010 to January 2020. Among 692 outbreaks reported from second-level administrative units (e.g., districts), the median attack rate was 0.8 per 1000 people (interquartile range (IQR), 0.3-2.4 per 1000), the median epidemic duration was 13 weeks (IQR, 8-19), and the median early outbreak reproductive number was 1.8 (range, 1.1-3.5). Larger attack rates were associated with longer times to outbreak peak, longer epidemic durations, and lower case fatality risks. Conclusions: This study provides a baseline from which the progress toward cholera control and essential statistics to inform outbreak management in sub-Saharan Africa can be monitored.